Targeted metabolomics reveals fatty acid abundance adjustments as playing a crucial role in drought-stress response and post-drought recovery in wheat - Ullah, Safi; Khan, Mudassar Nawaz; Lodhi, Sumaira Salahuddin; Ahmed, Iftikhar; Tayyab, Muhammad; Mehmood, Tariq; Din, Israr Ud; Khan, Majid; Sohail, Quahir; Akram, Muhammad (Frontiers in Genetics, 2022)
Drought stress is one of the abiotic stresses restricting plant development, reproductive growth, and survival. In the present study, the effect of drought stress and post-drought recovery of the selected local wheat cultivar, Atta Habib was studied. Wheat was grown for 16 days followed by drought stress for 7 days and allowed to recover for 7 days after removal of the drought stress. The same-aged untreated plants were also grown as a control. The effect of drought stress and post-drought recovery on morphology (root length, shoot length, root weight, and shoot weight), enzymatic activity, and fatty acid profile were analyzed. The results showed that shoot weight (93.1 mg), root weight (85.2 mg) and shoot length (11.1 cm) was decreased in the stressed plants but increased steadily in the recovered plants as compared to same-aged control plants. While root length showed a higher increase (14.0 cm) during drought stress and tend to normalize during the recovery phase (13.4 cm). The ascorbate peroxidase activity was increased in the stressed plants (5.44 unit/mg protein) as compared to control while gradually normalized in the recovery phase (5.41 unit/mg protein). Gas chromatography coupled with mass spectrometric analysis revealed abundance changes in important fatty acids such as palmitic acid, stearic acid, oleic acid, linoleic acid and linolenic acid. The palmitic acid (39.1 %) and oleic acid (2.11 %) increased in the drought-stressed plants while the reduction in linoleic acid (6.85 %) and linolenic acid (51.18 %) was observed as compared to the same-aged control plants i.e. palmitic (33.71%), oleic (0.95%), linoleic (7.52%) and linolenic acid (55.23 %). The results suggest that wheat tries to recover in the post-drought stage by repairing oxidative damage through ascorbate peroxidase, and adjusting fatty acids abundances under drought stress and during the post-drought phase as an effort to maintain membranes integrity and routing suitable fat metabolism, thus helping recovery. Targeted metabolomics may be further used to explore the role of other metabolites in the drought-stress response mechanism in wheat. Furthermore, the relatively less explored avenue of post-drought recovery needs more detailed studies involving multiple stress durations.